The Concept of Islamic Education for Children According to Syaikh Jamal Abdurrahman: A Review in The Islamic Parenting Book - Mislaini; Hoktaviandri (Al Bahri: Journal of Islamic Education, 2024)
Talking about educating and providing guidance is the best gift from parents to children, exceeding the value of the world and its contents. However, the implementation of education must be based on educational philosophy and theory. The purpose of Islamic education for children is to increase their spiritual potential so that they become human beings with noble character, faith, and fear of Allah SWT. This research uses a library research method, this research is natural and inductive. Data analysis uses a descriptive-exploratory model developed by Miles and Huberman, involving three stages of analysis: data reduction, data presentation, and conclusion drawn. Data reduction involves grouping and classifying data that is relevant to the problem being studied. Important aspects of Islamic education include material and evaluation of Islamic education for children. Many parents are confused about educating their children. Despite being careful, often parents feel.